2000
DOI: 10.1016/s0735-1097(00)00809-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of folic acid and antioxidant vitamins on endothelial dysfunction in patients with coronary artery disease

Abstract: Folic acid supplementation significantly improved endothelial dysfunction in patients with coronary atherosclerosis. Further clinical trials are required to determine whether folic acid supplementation may reduce cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
1
4

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(117 citation statements)
references
References 57 publications
6
106
1
4
Order By: Relevance
“…While previous studies have suggested that the benefits of folic acid on FMD are partly dependent on its homocysteine-lowering effect, 7,8 our present study suggests the effects are independent of homocysteine-lowering, confirming the findings of the other recent diabetic studies. 25,26 It has been realized that the oxidative stress of diabetes may lead to oxidation of tetrahydrobiopterin, an essential co-factor of eNOS, resulting in the uncoupling of the eNOS enzyme and a loss of NO availability.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…While previous studies have suggested that the benefits of folic acid on FMD are partly dependent on its homocysteine-lowering effect, 7,8 our present study suggests the effects are independent of homocysteine-lowering, confirming the findings of the other recent diabetic studies. 25,26 It has been realized that the oxidative stress of diabetes may lead to oxidation of tetrahydrobiopterin, an essential co-factor of eNOS, resulting in the uncoupling of the eNOS enzyme and a loss of NO availability.…”
Section: Discussionsupporting
confidence: 92%
“…Our FMD results demonstrate considerable inter-patient variation of FMD with a wide range of values noted with folic acid and placebo, which is similar to that seen in other studies which have used similar methodology. 7,8,21,23,25,[28][29][30] Despite this variability, our study was sufficiently powered to demonstrate the absolute 2.6% increase in FMD with as few as 18 patients in this cross-over design. 31,32 On the other hand, as our study was only powered according to the effect on FMD, this small sample size may have been insufficient to demonstrate a significant secondary effect on the inflammatory markers.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The subject of pharmacological treatment of endothelial dysfunction has been reviewed by myself and others recently (52,94,95). Suffice it to say, interventions associated with favourable cardiovascular outcomes have been associated with attenuation of endothelial dysfunction for the most part (96)(97)(98)(99)(100)(101). The notable exception to this is hormone replacement therapy, which has been associated with improvement in endothelium-dependent vasomotion, but not cardiovascular outcome.…”
Section: Relationship Of Endothelial Function To Risk Factors and Thementioning
confidence: 99%